Factors influencing millennials’ intention to accept e-wallet in Klang Valley, Malaysia - Mohd Salleh, Muhammad Syafiq; Che Musa, Normaziah; Chuah, Yeong Shen; Hii, Saan Chieng; Lee, Hui Yun; Ab. Ghani, Norliyana; Zokri, Nurul Syakirah (UiTM Cawangan Johor, 2023)
The objective of the research is to study the factors affecting millennials ' intention to accept e-wallet in Klang Valley, Malaysia. It would investigate the link between personal innovativeness, social influence, perceived compatibility and facilitating conditions with behavioral intention. The result of the study will contribute to the understanding of the factors that influence millennials' acceptance oft-wallet. Convenience sampling is used in this study, as samples are selected depending on the availability and willingness of respondents to provide feedback. 774 responses were collected through questionnaires distributed using google forms. This research has excellent internal consistency and dependability of the variables analysed. The result found that there are significant relationships between millennials ' intention to accept e-wallets with personal innovativeness, social influences, perceived compatibility and facilitating conditions.